Data Management, Analytics and Innovation Proceedings of ICDMAI 2018, Volume 2 - Balas, Valentina Emilia; Sharma, Neha; Chakrabarti, Amlan (Advances in Intelligent Systems and Computing,, 2019)
The volume on Data Management, Analytics and Innovations presents the latest high-quality technical contributions and research results in the areas of data management and smart computing, big data management, artificial intelligence and data analytics along with advances in network technologies. It deals with the state-of-the-art topics and provides challenges and solutions for future development. Original, unpublished research work highlighting specific research domains from all viewpoints are contributed from scientists throughout the globe. This volume is mainly designed for professional audience, composed of researchers and practitioners in academia and industry.